Efektivitas Penggunaan Dana Desa dalam Mitigasi Bencana di Gampong Ulee Lheue - Faried, Ade; Mukhra, Syazarwan; Raihan Kemalasari, Cut; Shihab, Muhammad; Hasanah, Lailatul (Program Studi Ilmu Administrasi Negara Bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
The Indian Ocean earthquake and tsunami of 2004, and particularly in Aceh, highlighted the high vulnerability of coastal communities to natural disasters. This study aims to analyze the effectiveness of Village Funds in developing disaster mitigation infrastructure and its impact on improving community welfare in Gampong Ulee Lheue, Banda Aceh. A descriptive qualitative approach is adopted, employing data collection techniques such as in-depth interviews, field observations, and documentation. Data are analyzed through an interactive model, including data reduction, data presentation, and conclusion drawing. The results show that the Gampong Ulee Lheue government has integrated disaster mitigation aspects into village infrastructure development, such as the construction of sea walls, evacuation routes, and disaster information boards. Village Funds have been allocated effectively with active community participation in planning and supervision. Positive impacts can be seen in increased awareness of disaster preparedness, as well as an increased sense of security and community welfare. The uniqueness of this study lies in its focus on evaluating the implementation of Village Funds for the development of disaster mitigation infrastructure in post-tsunami coastal areas a topic that has not received adequate attention. This study highlights the strategic role of village governments in managing Village Funds to build sustainable, resilient communities.